Renal perfusion evaluation by alternating current biosusceptometry of magnetic nanoparticles - Quini, Caio C. [UNESP]; Matos, Juliana F. [UNESP]; Próspero, André G. [UNESP]; Calabresi, Marcos Felipe F. [UNESP]; Zufelato, Nicholas; Bakuzis, Andris F.; Baffa, Oswaldo; Miranda, José Ricardo A. [UNESP] (Elsevier, 2015)
Alternating current susceptometry, a simple and affordable technique, was employed to study the sensitivity of this approach to assess rat kidney perfusion by the injection of 200 μL of magnetic nanoparticles with a concentration of 23 mg/mL in the femoral vein and the measurement of the signal above the kidney. The instrument was able to detect the signal and the transit time of the first and second pass were measured in five animals with average values of 13.6±4.3 s and 20.6±7.1 s.